2021
DOI: 10.3390/nu13030967
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Ketogenic and Mediterranean Study Diets in a Crossover Trial: The Keto–Med Randomized Trial

Abstract: Adherence is a critical factor to consider when interpreting study results from randomized clinical trials (RCTs) comparing one diet to another, but it is frequently not reported by researchers. The purpose of this secondary analysis of the Keto–Med randomized trial was to provide a detailed examination and comparison of the adherence to the two study diets (Well Formulated Ketogenic Diet (WFKD) and Mediterranean Plus (Med-Plus)) under the two conditions: all food being provided (delivered) and all food being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 55 publications
2
32
0
3
Order By: Relevance
“…The practical implications for motivating food factors and values within interventions has been recently examined by Eustis and colleagues [7]. In our own trials, we have found varying psychosocial, demographic, and environmental motivational factors regarding adherence to study diets [6,8,9].…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The practical implications for motivating food factors and values within interventions has been recently examined by Eustis and colleagues [7]. In our own trials, we have found varying psychosocial, demographic, and environmental motivational factors regarding adherence to study diets [6,8,9].…”
mentioning
confidence: 60%
“…Greater dietary adherence, regardless of the type of diet, is an important factor in weight-loss success and maintenance [3][4][5]. We recently conducted an intervention trial comparing a lowcarbohydrate (ketogenic) and a Mediterranean diet in which we published a separate methods and adherence paper [6]. Even when we were providing participants with a food delivery service for 4 weeks to maximize adherence to their research diets we observed a wide range of adherence variability among participants; overall adherence was shown to be similar, increasing internal validity.…”
mentioning
confidence: 99%
“…Furthermore, dietary interventions may be more acceptable to patients than long-term drug therapies, which have poor adherence in COPD ( 27 ). Conversely, despite the common conception that KD are not sustainable for patients, trials show that patients given adequate education and support adhere to and enjoy KD as much as other diets and standard of care ( 8 , 28 ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, emerging evidence from long-term KD intervention in humans supports that the ketone level was also attenuated in T2DM patients (Landry et al 2021 ). And the initial β-HB value was below ketosis level at the beginning of the KD treatment (0.12 mmol/L), then peaked at 1.1 mmol/L (4 weeks) and decreased to 0.51 mmol/L by week 12 in the end (Landry et al 2021 ). Moreover, β-HB levels are significantly different among different mice by KD intervention based on previous reports.…”
Section: Discussionmentioning
confidence: 99%